2023
DOI: 10.1038/s41467-022-34033-x
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 escape from cytotoxic T cells during long-term COVID-19

Abstract: Evolution of SARS-CoV-2 in immunocompromised hosts may result in novel variants with changed properties. While escape from humoral immunity certainly contributes to intra-host evolution, escape from cellular immunity is poorly understood. Here, we report a case of long-term COVID-19 in an immunocompromised patient with non-Hodgkin’s lymphoma who received treatment with rituximab and lacked neutralizing antibodies. Over the 318 days of the disease, the SARS-CoV-2 genome gained a total of 40 changes, 34 of which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…A study has found that a female patient diagnosed with immunodeficiency had continuous mutations of the virus in her body during infection, accumulating 40 mutations in total, which is far beyond the evolutionary rate of SARS‐CoV‐2 in the general population 23 . In this study, the mutations that occur in vitro without immune pressure are similar to the mutations that occur in the bodies of immunocompromised patients.…”
Section: Discussionmentioning
confidence: 56%
“…A study has found that a female patient diagnosed with immunodeficiency had continuous mutations of the virus in her body during infection, accumulating 40 mutations in total, which is far beyond the evolutionary rate of SARS‐CoV‐2 in the general population 23 . In this study, the mutations that occur in vitro without immune pressure are similar to the mutations that occur in the bodies of immunocompromised patients.…”
Section: Discussionmentioning
confidence: 56%
“…Our work, combined with Hamelin, Dolton’s and Swaminathan’s indicates that P→X mutations – which are now observed across Omicron variants that have infected large proportions of populations – in CD8+ T cell epitopes should be a priority for surveillance regarding T cell escape in HLA-B07 individuals and for associations with breakthrough infections. Overall, our data combined with recent studies are starting to indicate a more nuanced outlook regarding the impact of VOCs mutation on T cell responses, than the consensus [ 17 , 31 , 32 , 34 , 57 , 59 ].…”
Section: Discussionmentioning
confidence: 70%
“…However, not all HLA ligands can invoke T cell responses [ 38 , 39 ]. Furthermore, studies such as those of Naranbhai et al [ 17 ] and Reynolds et al [ 18 ] observed considerable numbers of patients with impaired T cell responses to Omicron infection [ 57 ]. Indeed, while widespread and complete escape is unlikely, it is plausible that detrimental mutations could impair certain individuals, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Even in mild and moderate cases of COVID‐19, most recovered individuals linger with long COVID‐19 42 . In the case of immunocompromised patients, a recent study has shown that in long COVID‐19, SARS‐CoV‐2 is capable of escaping cytotoxic T cell‐mediated immunity, suggestive of the continuous and perilous evolution of the virus in humans 43 . Alarmingly, this pandemic has also significantly enhanced the burden of many fatal infectious diseases like HIV (human immune deficiency virus) and TB (tuberculosis) 44,45 .…”
Section: Introductionmentioning
confidence: 99%
“…42 In the case of immunocompromised patients, a recent study has shown that in long COVID-19, SARS-CoV-2 is capable of escaping cytotoxic T cell-mediated immunity, suggestive of the continuous and perilous evolution of the virus in humans. 43 Alarmingly, this pandemic has also significantly enhanced the burden of many fatal infectious diseases like HIV (human immune deficiency virus) and TB (tuberculosis). 44,45 Therefore, it is of paramount importance to understand the disease-causing mechanism of SARS-CoV-2 to efficiently manage the disease and devise combat strategies.…”
mentioning
confidence: 99%